2021
DOI: 10.20473/imhsj.v5i3.2021.307-316
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Obesity, Twin-Pregnancy and Previous History of Preeclampsia With Preeclampsia

Abstract: Background: Preeclampsia can threaten the health of the mother and fetus during pregnancy and childbirth, besides that it also increases the risk of long-term complications and has the potential to cause death. The incidence of preeclampsia at the RSUD Engku Haji Daud Tanjung Uban showed an increase in the last three years, namely the occurrence from 2017 as many as 23 cases to 56 cases in 2019. The condition of preeclampsia can worsen quickly and without warning, for that, it must be detected and managed appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
0
0
2
Order By: Relevance
“…The results of this study contradict the results of research by Denantika, Serudji, and Revilla, which showed that the proportion of multigravidas who did not suffer from preeclampsia was 1.3 times higher than multigravidas who suffered from preeclampsia (21). Research by Parantika et al shows that there is no significant relationship between gravida status and the incidence of preeclampsia in mothers giving birth (22). Based on theory, primigravida have a greater risk of suffering from preeclampsia than multigravidas because this disease usually occurs in women who are first exposed to it, villi chorales.…”
Section: Discussioncontrasting
confidence: 98%
“…The results of this study contradict the results of research by Denantika, Serudji, and Revilla, which showed that the proportion of multigravidas who did not suffer from preeclampsia was 1.3 times higher than multigravidas who suffered from preeclampsia (21). Research by Parantika et al shows that there is no significant relationship between gravida status and the incidence of preeclampsia in mothers giving birth (22). Based on theory, primigravida have a greater risk of suffering from preeclampsia than multigravidas because this disease usually occurs in women who are first exposed to it, villi chorales.…”
Section: Discussioncontrasting
confidence: 98%
“…Based on the type of pregnancy, preeclampsia was the most common in single pregnancies, with 51 (94.44%) patients, in research conducted by Parantika et al (2021); there were 49 (87.5%) patients with single pregnancies and 7 (12.5%) patients with twin pregnancies who experienced preeclampsia. Preeclampsia can occur in single pregnancies due to several factors, such as a previous history of hypertension, the age of the pregnant woman who is at risk, or a lack of antenatal check-ups so that preeclampsia cannot be detected early.…”
Section: Results and Discussion Primary Characteristic Of Patientsmentioning
confidence: 99%
“…Hasil penelitian ini selaras dengan penelitian Nurhasanah (2017) dan Parantika (2021) yang mengatakan bahwa terdapat hubungan antara obesitas dengan kejadian preeklampsia. Ibu hamil dengan IMT >27 atau obesitas akan meningkatkan risiko preeklampsia 5,923 kali lebih besar dibandingkan ibu yang tidak obesitas (Widiastuti,…”
Section: Jember Medical Journal(jmj)unclassified